Highly twisted pyrene derivatives for non-doped blue OLEDs. (May 2016) - Lee, Sang Bong; Park, Kwang Hun; Joo, Chul Woong; Lee, Jeong-Ik; Lee, Jonghee; Kim, Yun-Hi
Abstract: New highly twisted rigid blue light-emitting materials were designed, composed of pyrene with a xylene core unit and either naphthalene or phenyl end units. These blue-emitting materials were synthesized via the Suzuki cross-coupling reaction and their structures were confirmed using FT-IR, 1 H NMR, 13 C NMR, and mass spectroscopy. The optical, electrochemical and thermal properties of the materials were investigated. The non-coplanar structure introduced by highly twisted xylene units provides steric hindrance, resulting in very deep blue emission. The fabricated devices exhibited a maximum external quantum efficiency (EQE) of 3.69% with CIE color coordinates (x, y: 0.15, 0.06). Graphical abstract: Highlights: Deep blue emitting materials based on pyrene core. Highly twisted blue emitting materials by xylene units. 3-Dimensionally highly twisted non-coplanar. Non-doped device using new pyrene exhibited efficiency of 3.69%. Non-doped EL devices showed high color purity of (0.15, 0.06).